2012
DOI: 10.1021/jm201708h
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of PG545: A Highly Potent and Simultaneous Inhibitor of Angiogenesis, Tumor Growth, and Metastasis

Abstract: Increasing the aglycone lipophilicity of a series of polysulfated oligosaccharide glycoside heparan sulfate (HS) mimetics via attachment of a steroid or long chain alkyl group resulted in compounds with significantly improved in vitro and ex vivo antiangiogenic activity. The compounds potently inhibited heparanase and HS-binding angiogenic growth factors and displayed improved antitumor and antimetastatic activity in vivo compared with the earlier series. Preliminary pharmacokinetic analyses also revealed sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
131
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(140 citation statements)
references
References 35 publications
6
131
1
2
Order By: Relevance
“…It has been previously demonstrated that the antitumor activity of HS mimetics is primarily mediated through the inhibition of growth factor binding and heparanase activity, which primarily effect tumor angiogenesis and metastasis (13,14,16,22,23,40,41). However, the potential effects of PG545 as an immunomodulatory agent have not been examined.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been previously demonstrated that the antitumor activity of HS mimetics is primarily mediated through the inhibition of growth factor binding and heparanase activity, which primarily effect tumor angiogenesis and metastasis (13,14,16,22,23,40,41). However, the potential effects of PG545 as an immunomodulatory agent have not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…Given the important role of heparanase and HS in cancer progression, HS mimetics that inhibit heparanase and compete for the HS-binding domain of angiogenic growth factors have been developed as novel antitumor agents (12,13). Indeed, HS mimetics have demonstrated antitumor activities in multiple preclinical studies of metastatic solid tumors in mice (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although PG545 appears as a potent inhibitor that attenuates the progression of several carcinomas (19) and lymphomas ( Fig. 1), it also exhibits heparanase-unrelated properties and impedes the signaling of HS-bound growth-and angiogenesispromoting factors (21). To evaluate the role of heparanase in lymphoma growth in a more specific manner, we used a polyclonal Ab (Ab 1453) that neutralizes heparanase enzymatic activity ( Fig.…”
Section: Inhibition Of Lymphoma Xenograft Growth By Heparanase-neutramentioning
confidence: 99%